Ongoing 5-year+ survival after multiple metastasectomies, followed by CAPOX plus bevacizumab, for metastatic colorectal cancer - Kozue Matsuishi; Yuji Miyamoto; Yukiharu Hiyoshi; Ryuma Tokunaga; Katsunori Imai; Hiromitsu Hayashi; Yoichi Yamashita; Naoya Yoshida; Hideo Baba (Surgical Case Reports, 2020)
Abstract Background Advancements in chemotherapy for metastatic colorectal cancer (mCRC) have improved long-term outcomes, and median survival currently exceeds 30 months. The recommended treatment for mCRC is multidisciplinary, including a combination of surgical resection and chemotherapy. In this study, we report the case of a patient who has survived for more than 5 years after an initial diagnosis of mCRC while undergoing first-line chemotherapy and six repeat metastasectomies. Case presentation A 55-year-old man was diagnosed at our hospital with sigmoid colon cancer and hepatic metastasis. We performed laparoscopic sigmoidectomy and hepatic segmentectomy (segment 5 [S5] and S8). After resecting the primary tumor and liver metastasis, other metastases were found. Together with perioperative chemotherapy (CAPOX + bevacizumab), we performed repeated metastasectomies for liver metastasis (S4 and S7), pulmonary S1 metastasis, aortic lymph node metastasis, and right adrenal metastasis. With six metastasectomies, the patient has survived for more than 5.5 years. Conclusions Multidisciplinary treatment extends survival and improves the quality of life in patients with mCRC. Planned surveillance after metastasectomy may also be necessary to promote the early detection of recurrence in these patients.